Quantitative definition of phenotypic variation in land snail shells - Jackson, H (2022)
The study of both animal colouration and patterning across the natural world has been imperative for understanding some of the key principles of biology throughout the past century, particularly with respect to evolution and genetics. Generally, colour and pattern have each been described qualitatively, often being binned into discrete groups relying on human perception of colour or pattern, rather than being considered in a biologically relevant context. ‘Binning’ traits into discrete groups has the consequence that variation within discrete morphs is often overlooked. Terrestrial gastropods, such as the selected study genera Cepaea and Auriculella, provide an ideal system for the study of polymorphisms and colour variation due to the extreme variety of morphs present across the taxa, as well as the nature of shell growth providing a complete ontogeny of an individual.